2017
DOI: 10.1007/s00586-017-4983-0
|View full text |Cite
|
Sign up to set email alerts
|

The current state of the evidence for the use of drains in spinal surgery: systematic review

Abstract: There is a paucity of published literature on the use of drains following spinal surgery. This is the first study to assess the evidence for the benefits of drains post-operatively in spinal surgery. The identified studies have shown that drains do not reduce the incidence of complications in anterior cervical discectomy and fusion, one and two level posterior cervical fusions, lumbar laminectomies, lumbar decompressions or discectomies and posterior spinal fusion for adolescent scoliosis. Further level I and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 27 publications
0
34
0
1
Order By: Relevance
“…24 However, Patel et al showed in their systematic review that drains do not reduce the prevalence of pSEH. 25 Ahn et al examined the diameter of the drains. They found larger drains did not prevent pSEH 26 compared with smaller drains.…”
Section: Prevalencementioning
confidence: 99%
“…24 However, Patel et al showed in their systematic review that drains do not reduce the prevalence of pSEH. 25 Ahn et al examined the diameter of the drains. They found larger drains did not prevent pSEH 26 compared with smaller drains.…”
Section: Prevalencementioning
confidence: 99%
“…Although it is agreed that the use of drains should decrease the incidence of postoperative hematoma formation and hence the incidence of infection, systematic reviews have shown a paucity of level I or II evidence suggesting benefits from the employment of drains in orthopedic 7 and in spinal surgery. 8 A prospective randomized study compared the results following single-level laminectomy with and without drain reaching the conclusion that the usage of drain did not affect the rate of complication 9 . The same conclusion was reported by an additional prospective randomized study performed on use of drain following extensive lumbar spine surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of evidence regarding the effectiveness of closed-suction drainage in spinal surgery. 8 Drainage is used to reduce the incidence of complications especially neurologic impairment as a result of hematoma formation or accumulation of exudative fluid and hence wound healing complication. 2 An additional benefit of drainage use in spine surgery may be the prevention of postoperative fibrosis and hence adhesions that may complicate decompression surgery and usually cause treatment failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being widely used, the effectiveness of drains in decreasing post-operative hematoma formation and infection has been recently been called into question (14)(15)(16)(17)(18)(19). A few studies have shown no difference in clinical outcomes and complications profile with and without drain use (10,(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)(26). Others have suggested that drain placement negatively impacts outcomes leading to significantly greater use of allogenic blood transfusions, post-hemorrhagic anemia (26) as well as prolonged length of hospital stay (LOS) (19).…”
Section: Introductionmentioning
confidence: 99%